Extracellular Production of the Oncolytic Enzyme, L-Asparaginase, by Newly Isolated Streptomyces sp. Strain NEAE-95 as Potential Microbial Cell Factories: Optimization of Culture Conditions Using Response Surface Methodology - E.-A. El-Naggar, Noura (Current Pharmaceutical Biotechnology, 2015)
L-asparaginase is an effective anti-neoplastic agent used in chemotherapy of acute lymphoblastic leukemia. One hundred and thirty actinomycete isolates were isolated from several soil samples collected from different localities in Egypt. All these isolates were purified and evaluated for their ability to produce L-asparaginase activity. Among them, strain NEAE-95 was selected and identified as Streptomyces parvus strain NEAE-95 based on morphological, cultural, physiological characteristics and 16S rRNA sequence. The sequence was deposited in the NCBI GenBank database under accession number KJ200341. L-asparaginase production by Streptomyces parvus NEAE-95 was optimized in shake flask culture. The Plackett–Burman statistical design was used for initial screening of sixteen factors for their significance on L-asparaginase production. Among the variables screened, incubation time, L-asparagine and yeast extract had significant effects on L-asparaginase production. The levels of these significant variables and their interaction effects were optimized by Box–Behnken statistical design. As a result, the maximal L-asparaginase production was achieved at the following fermentation conditions: g/L (dextrose 2, starch 20, L-asparagine 14, KNO3 2, yeast extract 2, K2HPO4 2, MgSO4.7H2O 0.1, NaCl 0.1, FeSO4.7H2O 0.01), pH 7, temperature 30°C, agitation speed 200 rpm, inoculum size 2%, v/v and incubation time 8 days.
Keywords: Box behnken design